Spectroscopic Properties and Judd-Ofelt Analysis of Eu3+ doped Ba-Na-B Glasses for Photonic Applications. Issue 1 (March 2021) - Luewarasirikul, N; Kaewkhao, J
Abstract: In this work, barium sodium borate glasses doped with europium ions were fabricated by melt-quenching technique with the compositions of 10BaO:25Na2 O:(65-x)B2 O3 :xEu2 O3 (where x = 0.0, 0.1, 0.5, 1.0, 1.5 and 2.0 mol%). The density, molar volume and refractive index were carried out at room temperature. The densities of the Eu 3+ -doped glass samples are around 2.6663 to 2.7850 g/cm 3, the molar volumes are around 28.5337 to 29.3455 cm 3 /mol and the refractive indexes are around 1.5379 to 1.5624. The absorption spectra, recorded in the UV-Vis-NIR region from 350 to 2500 nm, showed the highest peak at 393 nm (corresponding to the 7 F0 → 5 L6 transition) in Vis region. The emission spectra, observed with 394 nm excitation wavelength, showed the peaks centered at 590, 613, 652 and 700 nm (corresponding to the 5 D0 → 7 F1, 7 F2, 7 F3 and 7 F4 transitions, respectively). The luminescence lifetimes were found to be 1.948, 1.938, 1.924, 1.913 and 1.901 ms for 0.1, 0.5, 1.0, 1.5 and 2.0 mol% of Eu2 O3 doped in the glass samples, respectively. The color coordinates of the emitted light for all glass samples were found to be (0.65, 0.35) in the CIE 1931 chromaticity diagram (located in reddish orange region). The emission spectra showed that the glass with 1.5 mol% of Eu2 O3 provided the highest peak for all glass samples because of the concentration quenching effect. Judd-Ofelt analysis was also employed in this work to investigate the radiative properties of the glass samples.